Application of combined QSAR-ICE models in calculation of hazardous concentrations for linear alkylbenzene sulfonate. (August 2022) - Liang, Weigang; Wang, Xiaolei; Wu, Aiming; Zhang, Xiao; Niu, Lin; Wang, Junyu; Wang, Xia; Zhao, Xiaoli
Abstract: Linear alkylbenzene sulfonate (LAS) is a widely used anionic surfactant that exists as a mixture of various homologous structures in water environment. In the calculation of hazardous concentrations of LAS, cross-taxonomies toxicity estimation was often used instead of species-level-specific estimation for the normalization of toxicity data, which led to substantial uncertainties. In this study, combined quantitative structure–activity relationship (QSAR) and interspecific relationship estimation (ICE) models were developed to normalize the alkyl chain length of toxicity data and calculate the 5th percentile hazard concentrations (HC5 s) of LAS. Using seven acute QSAR models based on measured data and 29 acute QSAR-ICE models derived from them, the acute HC5 s of LAS were calculated as 2.09–3.67 mg/L. Furthermore, species- and family-level-specific QSAR and QSAR-ICE models were used to calculate chronic HC5 s (0.19–0.38 mg/L). Additionally, the sensitivity of biological toxicity to the hydrophobicity of LAS, represented by the slope of the QSAR models, had a significant correlation with the taxa of the species. Further risk assessment based on chronic HC5 s showed potential ecological risks in the Dianchi Lake basin and Haihe River basin in China, which should cause concern. Graphical abstract: Image 1 Highlights: The QSAR-ICE models were developed to calculate the HC5 s of LAS. Species- or family-level normalization was done to improve toxicity prediction. SSDs and HC5 s were generated to compare representative hazard assessment scenarios. The ecological risk of LAS in major basins in China was assessed for the first time.